سن الزواج في قانون الأحوال الشخصية لمسلمي الفلبين: دراسة مقارنة مع الفقه الإسلامي - تفسي، دار السلام تونجاياو (مركز البحث العلمي الاسلامي, 2022)
تناول هذا البحث موضوع سن الزواج في قانون الأحوال الشخصية لمسلمي الفلبين، دراسة مقارنة مع الفقه الإسلامي. حيث جاء القانون الفلبيني في المادة ‎16.‏ ونصت المادة في الفقرة (1) "أي مسلم بلغ عمره خمس عشرة سنة على الأقل..." وهذا يدل على موضوع هذا البحث في هذه الدراسة وغيرها من المواد التي تتعلق بها. تناول هذا البحث موقف هذا القانون فيها توضيحا وتوثيقا بذكر قوانين بعض الدول العربية مقارنا مع الفقه الإسلامي. وذلك بتناوله التعريف الفقهي للزواج، وما يتعلق به كمشروعيته وأهليته، وحكم زواج الصغير والصغيرة، وما به من الأحكام الفقهية في مسألة سن الزواج علما أنها تعتبر مسألة من المسائل المستجدة المختلف فيها بين الفقهاء المعاصرين؛ ولهذا لابد به من تحرير محل النزاع والأدلة لتتضح معالمها وحدودها ولئلا تشتبه بغيرها ولا يدخل فيها ما ليس منها. وبعد عرض أقوال وآراء الفقهاء ومناقشة أدلتهم فيها، خلص البحت إلى صحة تزويج الصغار قبل البلوغ في العصر القديم مع مراعاة الضوابط والشروط الشرعية، وأما ما وقع في العصر الحاضر فقد خلص البحت إلى جواز تحديد سن الزواج وذلك بإرجاع الأمر إلى ولي الأمر في قانون الدولة، ويجوز للقانون إصدارة للمصلحة الراجحة. وقد أوصى الباحث بعناية وتوضيح نص قانون الأحوال الشخصية لمسلمي الفلبين على أن لا يخالف آراء العلماء في الفقه الإسلامي في مسألة سن الزواج وغيرها ليكون أكثر فعالية للجميع كأكثر قوانين الدور العربية والإسلامية. This research dealt with the issue of the age of marriage in the Code of Muslim Personal Laws of the Philippines, a comparative study with Islamic jurisprudence, where the law came in Article 16 and the article stated in Paragraph (1) “Any Muslim male at least fifteen years of age…” This indicates the title of this research in this study, and other articles related to it, (This study) dealt with the position of this law in it, with an explanation that mentions the positions of the laws of some Arab countries, in comparatives with Islamic Jurisprudence by dealing with the Jurisprudential definition of marriage, and what is related to it such as its legitimacies, eligibilities and the rules of minors (Young man and young woman), and what is related to it is one of the Jurisprudential rulings on the issue of the age of marriage, knowing that it is considered one of the emerging issues in which the contemporary Jurists differ, and for this it is necessary to liberate the subject of disputes and the evidences so that its features and limits are clear, and it is not suspected of other than it and to reject which is not included in it. After exposing the sayings and opinions of Jurists and discussing their evidences, the research concluded that the marriage of young children before puberty is lawful, with taking the controls and conditions of legitimacy in the ancient era and the lack of determining the age of marriage. In this present era, the research concluded that it is permissible to determine the age of marriage by referring the matter to the affairs of the guardian in the law of the state, and the law may issue it for the preponderant interest, The researcher recommended an encouragement for someone to pay attention to the text of the Code of Muslim Personal Laws of the Philippines, provided that it does not contradict the opinions of scholars in Islamic Jurisprudence on the issue of the age of marriage and others, in order to be more effective for all, as most of the laws of Arab and Islamic countries.
Keywords: فقه الزواج -- الأحكام الفقهية -- قانون الأحوال الشخصية -- مسلمو الفلبين